2022
DOI: 10.3390/jcm11123288
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Consensus Clustering of Morbidly Obese Kidney Transplant Recipients in the United States

Abstract: Background: This study aimed to better characterize morbidly obese kidney transplant recipients, their clinical characteristics, and outcomes by using an unsupervised machine learning approach. Methods: Consensus cluster analysis was applied to OPTN/UNOS data from 2010 to 2019 based on recipient, donor, and transplant characteristics in kidney transplant recipients with a pre-transplant BMI ≥ 40 kg/m2. Key cluster characteristics were identified using the standardized mean difference. Post-transplant outcomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Artificial intelligence and machine learning (ML) have been applied in medicine to develop clinical decision support tools that can improve and individualise healthcare, including organ transplantation 29–36. Unsupervised consensus clustering is ML adopted to identify novel data patterns and distinct subtypes 37–39.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence and machine learning (ML) have been applied in medicine to develop clinical decision support tools that can improve and individualise healthcare, including organ transplantation 29–36. Unsupervised consensus clustering is ML adopted to identify novel data patterns and distinct subtypes 37–39.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) have been increasingly applied to individualized medicine [ 21 , 22 , 23 , 24 , 25 , 26 ], including the prediction of AKI in various settings [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. ML algorithms can handle nonlinear, complex, and multidimensional data [ 36 , 37 ], and recent studies have shown high predictive performance from ML algorithms that outperform traditional statistical analyses [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is a subfield of artificial intelligence that has been applied to assist clinicians in making better clinical decisions in various areas of the medical field [41][42][43]. Generally, machine learning provides three types of algorithms: supervised, unsupervised, and reinforcement learning [41][42][43]. By identifying certain similarities and differences in various input variables, a computer system can complete a task without explicit programming.…”
Section: Introductionmentioning
confidence: 99%
“…By identifying certain similarities and differences in various input variables, a computer system can complete a task without explicit programming. This is known as unsupervised machine learning [41][42][43][44]. As a result, grouping data into clinically relevant clusters can aid clinicians [42,43,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation